A Survey of Reflections of Death, Situation and Boundary Situations in Contemporary Poetry of Iran: A Case Study of Shams Langeroodi\'s Poetry - سجاد Sadeqvand; Qodratollah Taheri (فصلنامه نقد ادبی, 2023)
Existentialism is one of the most important contemporary philosophical currents, widely reflected in literature; situation, Boundary Situations and death are major existential concepts. In this paper, the reflection of the above concepts in the poems of Shams Langeroodi was surveyed. The results and numerous examples show that firstly, these concepts were reflected to a great extent in the studied poems; secondly, these concepts were reflected through artistic logic and poetic arrangements; and thirdly, some approaches and subdivisions can be seen among the results. Four existentialist approaches to death can be seen among the poems, which are, in order of frequency, as follows: 1. Death as a phenomenon that causes decay, ending, and termination 2. Death as a fact and as a boundary situation. 3. Death and anxiety 4. Death and absurdity and futility. Among Boundary situations, suffering is the most significant. The poet has reflected on the concepts from a variety of perspectives, and therefore the existentialist approach of the poems cannot be fully traced back to a particular thinker. Extended Abstract Introduction The philosophy of existentialism is a philosophy of life and deals with serious and decisive, not abstract and distant issues. As a result, these concepts have found wide acceptance in art, literature, and poetry. Concepts such as situation, boundary situations, and death are found primarily in the works of thinkers from this field. The attention to objective themes may be one of the reasons for the popularity and popularity of this movement. It seems that contemporary literary works, which are called successful works, contain these concepts in some parts. And in contemporary Iranian literature and poetry, a considerable number of creative works had (and have) significant existentialist concerns, and under certain conditions, one can see the reflection of existential considerations in their works. Existentialism in Shams Langeroodi's poems and, of course, existential death, situation and boundary situations in his poems have not been studied yet. Theoretical Framework and Methodology The purpose of this article was to examine the reflections of the above existential concepts in the poems of Shams Langeroodi. Therefore, the concepts of death, situation and boundary situations in the works of the most important thinkers of the philosophy of existentialism were first examined, and then the presence of these concepts in the above poems and the poet's main approaches to this concept were studied through examples. It seems that these concepts are among the most common existentialist concepts of the aforementioned poets and show considerable diversity. Due to the attention that thinkers such as Heidegger, Sartre, and Jaspers paid to the mentioned concepts, their works were examined in order to establish a framework for the analysis of the poems. Findings, Discussion and Conclusion The results show that all these three existential concepts are frequent in Shams Langeroodi's poems. The concept of death has been reflected in detail in four existential approaches: 1. dissolving, terminating and annihilating death 2. death, a reality and a boundry situation 3. death and sorrow 4. death, futility and despair. As for the number of poems, there are relatively many examples of terminating and annihilating death. As for the boundry situations, besides death, the boundry situation of suffering is reflected most often. The diversity of the poet's existential approaches to these three concepts is one of the obvious findings of this study. His poems reflect the many existential tendencies to which he is exposed, and, of course, he has always kept in mind that he is a poet and that his work is different from philosophizing; therefore, his poetry contains a number of existentialist theories in which the concepts of the main existentialist thinkers are reflected. Therefore, his poetry cannot be completely attributed to a particular philosopher, and, of course, the poet's emphasis in the poems under study is on "being a poem".